THE APPLICATION OF FLYWHEEL MARKETING IN MARKETING STRATEGY AND ITS IMPLEMENTATION ON THE BUSINESS MODEL CANVAS: A CASE STUDY OF NASI KEBULI DASUKI - Maulidian; Zahra, Salwa Fatima (Jurnal Agroekoteknologi dan Agribisnis, 2025)
MSMEs in Indonesia's culinary sector face increasingly complex competitive challenges due to product similarities and shifting consumer preferences. In this context, this study aims to develop a customer-centered marketing strategy by integrating the flywheel marketing approach into the Business Model Canvas (BMC) framework for the Nasi Kebuli Dasuki MSME. This research employed a descriptive qualitative method with SWOT analysis to identify the strengths, weaknesses, opportunities, and threats faced by the business. The results of IFAS and EFAS analysis indicated that Nasi Kebuli Dasuki is positioned within an aggressive strategy quadrant, enabling the use of internal strengths to seize external opportunities. The proposed marketing strategy adopted a flywheel approach through three key stages: attract (drawing in customers), engage (building involvement), and delight (maintaining loyalty), all of which were systematically mapped into the nine BMC elements. Key findings demonstrate that this strategy effectively enhances customer loyalty, expands market reach through digital channels, and adds value through environmentally friendly practices and strong customer service. This study concludes that the flywheel marketing strategy offers a relevant and sustainable approach to supporting MSME growth in the digital era, especially within Indonesia's local culinary sector.